Young learners - Phillips, Sarah (Oxford University Press, 1993)
English lessons form an integral part of a young learner's whole education. This book ciontains guidance for teachers who are new to young learners, and ideas and materials for a wide variety of language practice activities, including art and crafts, drama, games, storytelling, and songs. This book is intended for teachers of English as a foreign language.